2015
DOI: 10.1515/bnm-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterned freestanding magnetron sputtered Mg-alloy scaffolds

Abstract: Freestanding scaffolds were fabricated of Mg5W (wt.% yttrium) alloy using magnetron sputtering technology. Appropriate method was found to produce scaffolds with high reproducibility, spatial resolution of 1 μm and good mechanical properties. Two different techniques were used for surface finishing, microblasting and chemical polishing. SEM investigation showed high surface quality after chemical polishing while microblasting influenced mechanical properties of the Mg5W alloy. Magnetron sputtering offers a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Potassium hydroxide (KOH) (20%) was used to etch selectively the sacrificial AlN layer to achieve the free standing dog-bone shaped samples. Further details on the fabrication process can be found in (Haffner et al, 2015).…”
Section: Experimental Fabricationmentioning
confidence: 99%
“…Potassium hydroxide (KOH) (20%) was used to etch selectively the sacrificial AlN layer to achieve the free standing dog-bone shaped samples. Further details on the fabrication process can be found in (Haffner et al, 2015).…”
Section: Experimental Fabricationmentioning
confidence: 99%
“…Recent studies by Zamponi, de Miranda, and Siekmeyer et al [ 40 , 41 , 42 , 43 ] showed that magnetron sputtering can be used to fabricate in situ structured and freestanding NiTi foils. Schlüter and Haffner et al [ 44 , 45 , 46 , 47 ] demonstrated that this method can be used as well for freestanding, biodegradable Mg-based devices. It was shown that the technique allows the fabrication of scaffold devices with a film thickness up to 250 µm and minimal feature sizes of 5 µm [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Schlüter and Haffner et al [ 44 , 45 , 46 , 47 ] demonstrated that this method can be used as well for freestanding, biodegradable Mg-based devices. It was shown that the technique allows the fabrication of scaffold devices with a film thickness up to 250 µm and minimal feature sizes of 5 µm [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…The usage of magnetron sputtering in combination of UV lithography for the fabrication of NiTi devices for medical applications was first shown by Zamponi, Siekmeyer, and de Miranda et al [ 16 , 17 , 18 , 19 ]. Furthermore, the method was adapted by Schlüter and Haffner et al for the fabrication of biodegradable Mg-based devices with feature sizes down to 5 μm [ 20 , 21 , 22 , 23 ]. In other work, the technique was used for the fabrication of biodegradable FeMn foils.…”
Section: Introductionmentioning
confidence: 99%